AN ANALYSIS OF CAREER DEVELOPMENT OF WOMEN CIVIL SERVANTS (PNS) IN MINISTRY OF FINANCE - Sonya Elfadhila; Teguh Kurniawan (NATAPRAJA, 2020)
In global there has been an increase in the number of women who work in the public sector including Indonesia. However, it did not have much effect on the number of women civil servant representation in high managerial or structural positions as part of career development in PNS Management. This condition is also faced by the Ministry of Finance, which have a high commitment to the implementation of pro-gender staff development policies. This study aims to find out how the career development of women civil servants in the Ministry of Finance through the post-positivism approach uses qualitative methods with literature studies and in-depth interviews with officials related to career development. Theories from Viki and Fiona regarding women's career development through individual and organizational aspects are used in conducting analyzes. The results showed that the career development of women civil servants in the Ministry of Finance had not been running optimally. The high number of male civil servants affects the low number of women civil servants who will occupy higher-level structural positions.  Furthermore, it can be seen in the individual variables that there is still a lack of interest in female civil servants participating in education and training, and also not all female civil servants get female mentors who can become a role models because mentors are direct supervisors of employees.  while the organizational variables indicate that there are still gender issues faced by female civil servants in the Ministry of Finance.